PENGARUH KOMPENSASI DAN JOB SECURITY TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI KONTRAK SATUAN POLISI PAMONG PRAJA DAN WILAYATUL HISBAH KOTA BANDA ACEH - Cut Devi maulidasari; Riznal Akhyar (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2019)
ABSTRACTThe purpose of this study was to determine the effect of compensation and job security on workmotivation and its impact on the performance of the Contract Employees Civil Service Police Unitand Wilayatul Hisbah Banda Aceh. Data analysis is the process of simplification of data into aform that is easier to read and implement. The method chosen to analyze the data must match thepattern of research and variables to be studied. This study using Structural Equation Modeling(SEM) with a research tool or software such as Partial Least Square (PLS) from the research thathas been done through observation and secondary data it can be concluded that compensation, jobsecurity, work motivation and employee performance contracts Police Unit Praja dan WilayatulHisbah Banda Aceh still not good, then the hypothesis 1 is rejected. From the research that hasbeen done can be concluded that the hypothesis that compensation and job security simultaneouslyand partially effect on work motivation can be received from the research that has been done canbe concluded that hypothesis stating that compensation and job security simultaneously andpartially effect the performance is acceptable. From the research that has been done can beconcluded that the hypothesis that motivation influence on work motivation can be accepted. Theresult of this research of which it can be concluded that the hypothesis of compensation and jobsecurity simultaneously and partially influence performance through work motivation isacceptable.Keywords: Compensation, Job Security, Work Motivation, Performance